2006
DOI: 10.1002/app.24571
|View full text |Cite
|
Sign up to set email alerts
|

PSA performances and viscoelastic properties of SIS‐based PSA blends with H‐DCPD tackifiers

Abstract: Hotmelt pressure sensitive adhesives (PSAs) usually contain styrenic block copolymers like styrene-isoprene-styrene (SIS), SBS, SEBS, tackifier, oil, and additives. These block copolymers individually reveal no tack. Therefore, a tackifier is a low molecular weight material with high glass transition temperature (T g ), and imparts the tacky property to PSA. The SIS block copolymer with different diblocks was blended with hydrogenated dicyclopentadiene (H-DCPD tackifier), which has three kinds of T g . PSA per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…With this method of adhesiveness measurement, it was evident that differentiation between the two surfaces of different adhesion properties could be determined. In addition, measurements determined in the current study were in the same order of magnitude as probe studies previously reported with similar materials which been reported to lie in the range of 0.1 to 2 N (31,40,41).…”
Section: Resultsmentioning
confidence: 81%
“…With this method of adhesiveness measurement, it was evident that differentiation between the two surfaces of different adhesion properties could be determined. In addition, measurements determined in the current study were in the same order of magnitude as probe studies previously reported with similar materials which been reported to lie in the range of 0.1 to 2 N (31,40,41).…”
Section: Resultsmentioning
confidence: 81%
“…For the cases of 12‐phr incorporation of tackifiers, the peaks of tan delta slightly shifted toward higher temperature: −43, −41, and −40°C for the gum‐rosin‐, phenolic‐resin‐, and petroleum‐resin‐filled vulcanizates, respectively. This is due to the fact that the T g s of most solid‐form tackifiers lies at much higher temperature than that of the base rubber [15, 16], thereby bringing about the shift of the T g of a particular system to higher temperature. In the molecular‐level point of view, the increase in T g implies that the presence of tackifier causes the reduction in free volume within the matrix [14].…”
Section: Resultsmentioning
confidence: 99%
“…The polymer/tackifier/plasticizer ratio was 45%/49%/6% in all PSAs. Lim et al . found that at tackifier contents between 30% and 50%, PSAs achieve highest peel strength.…”
Section: Methodsmentioning
confidence: 99%